Study on the indole acetic acid bio-production ability of the bacterium strain Rhizobium sp. 3.4 - Huong, Duong Giang; Dung, Nguyen Lan (Academia Journal of Biology, 2006)
The bacterium strain Rhizobium sp. 3.4, isolated from root nodules of green gram collected in Hatay province, had the ability to produce indole-3-acetic acid (IAA). The optimal conditions for the growth of this strain have been determined at 30oC and at pH 6. The influence of the culture of this strain on the leguminous seed germination was also studied and the final results showed that the culture of the strain Rhizobium sp. 3.4 at 10%, 20% and 30% had the effectiveness on stimulating the germination of soybean and cowpea seeds.